2022
DOI: 10.3390/app12125815
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular View on Biomaterials and Dental Stem Cells Interactions: Literature Review

Abstract: Biomaterials and stem cells are essential components in the field of regenerative medicine. Various biomaterials have been designed that have appropriate biochemical and biophysical characteristics to mimic the microenvironment of an extracellular matrix. Dental stem cells (DT-MSCs) represent a novel source for the development of autologous therapies due to their easy availability. Although research on biomaterials and DT-MSCs has progressed, there are still challenges in the characteristics of biomaterials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 110 publications
(143 reference statements)
0
3
0
Order By: Relevance
“…Several in vitro studies have shown that mechanical stimulation, such as that induced by collagen I hydrogel contraction, induces differentiation of mesenchymal stem/progenitor cells into osteoblasts [41,42], which also explains the high activity of ALP. At the same time, odontoblast differentiation under the influence of mechanical forces is shown in 3D scaffolds only for DPSCs [43][44][45].…”
Section: Discussionmentioning
confidence: 91%
“…Several in vitro studies have shown that mechanical stimulation, such as that induced by collagen I hydrogel contraction, induces differentiation of mesenchymal stem/progenitor cells into osteoblasts [41,42], which also explains the high activity of ALP. At the same time, odontoblast differentiation under the influence of mechanical forces is shown in 3D scaffolds only for DPSCs [43][44][45].…”
Section: Discussionmentioning
confidence: 91%
“… 78 In recent years, the use of fibrin in combination with synthetic or natural polymers has been investigated as a potential solution to this issue. 79 81 Other potential solutions include the use of solid scaffolds and their chemical modifications.…”
Section: The Use Of Fibrin Hydrogels In Tissue Engineering: Challengesmentioning
confidence: 99%
“…Also, the advances in research into the interactions between these biomaterials and the molecular components involved (mechanosensors and mechanotransduction) in DT-MSCs during their proliferation and differentiation were analyzed. The authors concluded that these kinds of biomaterials can contribute to research into regenerative medicine and the development of autologous stem cell therapies [8].…”
mentioning
confidence: 99%